2017
DOI: 10.18632/oncotarget.19996
|View full text |Cite
|
Sign up to set email alerts
|

Selective secretion of microRNAs from lung cancer cells via extracellular vesicles promotes CAMK1D-mediated tube formation in endothelial cells

Abstract: Extracellular vesicles (EVs) are key signaling mediators between cancer cells and their supporting stroma, and regulate critical processes such as invasion, metastases, and angiogenesis. We have identified a subset of miRNAs (miR-142-3p, miR-143-3p, miR-145-5p, miR-150-5p, miR-223-3p, miR-451a, miR-486-5p, miR-605-5p) that are enriched in lung adenocarcinoma extracellular vesicles compared to the donor cells from which they were derived. Two well-known tumor suppressors, miR-143-3p and miR-145-5p, were also en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…Previously we have demonstrated that miR‐142‐3p is selectively enriched by >4‐fold in the EVs derived from LAC cells compared to the donor cell . EV extraction was verified by Western blot for CD81 and TSG101 (Supplemental Figure S1).…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Previously we have demonstrated that miR‐142‐3p is selectively enriched by >4‐fold in the EVs derived from LAC cells compared to the donor cell . EV extraction was verified by Western blot for CD81 and TSG101 (Supplemental Figure S1).…”
Section: Resultsmentioning
confidence: 77%
“…EV extraction was verified by Western blot for CD81 and TSG101 (Supplemental Figure S1). Three of the five cell lines analyzed (H1437, H2073, H2228) did not have detectable quantities of miR‐142‐3p in the cellular RNA fraction, indicating a very efficient EV packaging mechanism as the EV's from these lines show enriched levels of miR‐142‐3p that accumulates in the donor cell when EV release is blocked . MiR‐142‐3p was detectable in the remaining intracellular fraction of cell lines (H1395 and H2347), but still showed a >18‐fold increase in the corresponding EVs .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Accumulating evidence has demonstrated that a large amount of exert critical effects on the progression and development of NSCLC. 8 miR-605-5p may enhance transactivation of p53 by inhibiting MDM2 in lung and breast cancer cell lines. 6 Accumulating evidence has shown the important role of miRNAs in cancer, including NSCLC, and suggests miRNAs to be biomarkers in NSCLC treatment.…”
Section: Introductionmentioning
confidence: 98%